2014
DOI: 10.1017/s0030605313001002
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of locally run conservation initiatives in north-east Peru

Abstract: Amazonas and San Martin are two of the most densely populated regions in rural Peru and have some of the highest deforestation rates in the country. They are also home to many threatened and endemic species and are considered a high priority for conservation. Under Peruvian law individuals and community groups can create private conservation areas and conservation concessions, and we evaluated the successes and challenges experienced in the creation and management of such areas, using direct observation, quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 64 publications
0
60
0
Order By: Relevance
“…More funding and improved management of existing PAs is required to successfully meet conservation targets (Gray et al, 2016;Waldron et al, 2013;Watson et al, 2014) and all types of private/communal PAs should appear in national strategies and action plans (Butchart et al, 2015). The additional coverage provided to Threatened species and ecoregions by private/communal PAs could provide increased protection in priority areas where traditional, large, state PAs are not viable (Butchart et al, 1995;Horwich et al, 2013;Horwich et al, 2015;Shanee et al, 2014). It must be highlighted that we did not include any measure of quality of protection or management in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More funding and improved management of existing PAs is required to successfully meet conservation targets (Gray et al, 2016;Waldron et al, 2013;Watson et al, 2014) and all types of private/communal PAs should appear in national strategies and action plans (Butchart et al, 2015). The additional coverage provided to Threatened species and ecoregions by private/communal PAs could provide increased protection in priority areas where traditional, large, state PAs are not viable (Butchart et al, 1995;Horwich et al, 2013;Horwich et al, 2015;Shanee et al, 2014). It must be highlighted that we did not include any measure of quality of protection or management in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We recommend that conservation planners and funders focus more attention on the benefits of private/communal PAs. In Peru formal registration of private conservation initiatives is hindered by a complex and expensive legal process which discourages creation of private/communal PAs (Shanee, 2016;Shanee et al, 2014;Shanee et al, Submitted). Facilitating legal mechanisms to ease the creation, management and reporting requirements would ease the burden on local stakeholders who often lack the proper education and access to economic resources currently required.…”
Section: Discussionmentioning
confidence: 99%
“…For example, used hunting registries and transects to assess spatial, seasonal, and taxonomic variations in sustainable hunting to inform conservation in the designated Pacaya-Samiria National Reserve in northeastern Peru. In the same region, ethnographic methods (key-informant interviews and participant observation) revealed that campesinos enacted communal rules in undesignated conservation concessions and private PAs to control hunting (Shanee et al 2015), which aligned with Bodmer et al's (2000) recommendation for Pacaya-Samiria. This example signals the value of the use of diverse methods to access campesino hunting across contexts and settings, even in the same region of the same country.…”
Section: Campesino Hunting Publication Trendsmentioning
confidence: 82%
“…In particular, such indices and other forms of harvest data, even with their respective limitations (Weinbaum et al 2013), can help researchers and campesinos themselves avert assumptions and conflicts about campesinos hunting through Conservation Biology Volume 34, No. 2, 2020 communal norms and regulations (Oliva et al 2014;Shanee et al 2015).…”
Section: Target Species and Hunting Sustainabilitymentioning
confidence: 99%
“…Stricter controls on extraction of natural resources from the forest are highly recommended to prevent further habitat loss (Anzures-Dadda and Manson 2007; Arroyo-Rodríguez and Dias 2010). In these highly threatened habitats, local support for conservation is vital to effective conservation, which can be achieved through environmental projects (Horwich et al 2012;Shanee et al 2014). Permanent community engagement is needed to increase local knowledge and foster a perception of ownership, which could lead to better protection of the area and improve the conservation status of primate populations.…”
Section: Discussionmentioning
confidence: 99%